Multiplying possibilities: A postdevelopment approach to hygiene and sanitation in Northwest China - Dombroski KF (Massey University, 2015)
Postdevelopment thinkers and writers have critiqued development discourse for its role in perpetuating inequality. In water, hygiene and sanitation (WASH) literature and interventions, the discourse used perpetuates inequality through classing anything other than private toilets as ‘without sanitation’. This implies that the people who use forms of hygiene and sanitation relying on collective toilets and alternative strategies are somehow unhygienic. Yet residents of Xining (Qinghai Province, China) rely on hygiene assemblages that do not always include private toilets, but nonetheless still work to guard health for families with young children. In this paper, I develop a postdevelopment approach to hygiene and sanitation based on starting with the place-based hygiene realities already working to guard health in some way, then working to multiply possibilities for future discursive and material hygiene realities. In this approach, contemporary and future realities may look quite different from those based on private toilets.
CAUL read and publish agreement 2022
Keywords: hygiene, assemblages, sanitation, water, development, post-development; 1604 Human Geography; 1606 Political Science